Typing of hemotropic Mycoplasma in Egyptian cats: first detection and phylogenetic analysis of Candidatus Mycoplasma turicensis - Mahmoud S. Safwat; Noha M. Bakry; Amany D. Bahr; Ahmed Orabi; Asmaa A. Rayan; Ghada M. Khalil; Salma W. Abdelhaleem; Omnia H. Refaei (Veterinary Research Communications, 2025)
Mycoplasma haemofelis (Mhf), Candidatus Mycoplasma haemominutum (CMhm), and Candidatus Mycoplasma turicensis (CMt) are the major feline hemotropic Mycoplasma (FHM) species identified in cats worldwide. Data concerning FHM in Egypt is limited; therefore, the current study aimed to gain further insights into disease epidemiology by investigating FHM molecular prevalence, risk factors, and hemogram abnormalities in 246 Egyptian cats (shelter-housed and client-owned) during 2022–2024. Additionally, 16 S rRNA gene-based maximum-likelihood (ML) phylogenetic analysis was performed for all CMt-positive samples for the first time in Egypt. FHM was detected in 16.3% ( n = 40) of cats and typed as CMhm, Mhf, and CMt in 15.4% ( n = 38), 3.6% ( n = 9), and 2.4% ( n = 6) of cats, respectively. Single CMhm and Mhf infections were detected in 12.6% ( n = 31) and 0.8% ( n = 2 ) of cats, respectively. Dual (Mhf and CMhm) and triple (Mhf, CMhm, and CMt) infections were found in 0.4% ( n = 1) and 2.4% (n = 6 ) of cats, respectively. CMhm was significantly associated with single infections rather than coinfections compared to other FHM species. Male sex and anemia were identified as predictors of FHM PCR positivity. FHM-infected cats had significantly lower hematocrit %, RBC counts, and hemoglobin concentrations than non-infected ones. Egyptian CMt sequences showed 97.6–100% nucleotide identity with each other. Egyptian and reference CMt strains represented nine nucleotide sequence types clustered into three well-supported clades on the ML tree without clear geographic distinction. The data generated in this study, conducted in Egypt, is crucial for enhancing our understanding of disease epidemiology and implementing effective preventive measures.